Revealing The Significant Role Of Stakeholders Post-Determination Customary Forest Management In The Serampas Customary Law Community, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
After determining customary forests, consistent assistance must be provided by the central and regional governments to ensure that customary forest management's ecological, economic, and socio-cultural functions can be sustainable. This research aims to analyze the role of parties in post-determination customary forest management in the Serampas customary law community (MHA), Jambi, Indonesia. This research uses a qualitative approach method, with Mitchell's stakeholder analysis concept. Data was collected using in-depth interviews, field observations, literature studies, and focus group discussions. This research shows that the parties, after determining customary forests, which have the potential for collaboration, are the definitive stakeholders, namely the regional government, village government, and village-owned enterprises (BumDes). Each party has a high interest (positive urgency) because the interests positively impact all stakeholders, can enhance the community's economy, and show high social benefits. If the three cannot work together well, potential conflicts can occur bilaterally and/or in alliances between U+ (positive urgency) owners, namely the regional government, village government, and BumDes. The relationship between NGOs and MHA will become dangerous stakeholders if each has high interests without considering the sustainability of customary forests and without supervision from other stakeholders.